EFL learners' use of question constructions over time: Patterns and proficiency effects. (June 2016) - Nekrasova-Beker, Tatiana
Abstract: A few studies have examined whether second language (L2) learners' lexico-syntactic development followed the predicted path of construction development from relying on formulaic patterns to gradually developing more abstract exemplars, but the results have been inconclusive. This study reports the results of quantitative and qualitative analyses conducted to track the development of English question constructions in EFL learners (N = 7) from lower-, mid-, and higher-proficiency levels. The purpose of the study was to examine if the patterns of the (wh-) aux-do construction used by participants at different proficiency levels became more productive over time. Participants' questions produced over a period of 32 weeks were analyzed using AntConc to identify specific instances of the (wh-) aux-do construction for each participant and each data collection session. The results indicated that while all participants' relied on several frequent patterns when asking questions, learners at the three proficiency levels were at different stages of pattern analysis.